2015
DOI: 10.1016/j.aop.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Deformations of the spin currents by topological screw dislocation and cosmic dispiration

Abstract: We study the spin currents induced by topological screw dislocation and cosmic dispiration. By using the extended Drude model, we find that the spin dependent forces are modified by the nontrivial geometry.For the topological screw dislocation, only the direction of spin current is bended by deforming the spin polarization vector. In contrast, the force induced by cosmic dispiration could affect both the direction and magnitude of the spin current. As a consequence, the spin-Hall conductivity doesn't receive c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…The common point between these areas of physics is the description of these defects made by the Volterra process [1,2,4,5]. Up to now, a great deal of study has explored quantum system in the presence of disclinations [6][7][8][9][10] and screw dislocations [5,[11][12][13][14][15][16] in the context of condensed matter physics. In particular, torsion effects related to the presence of topological defects are in the interests of studies of semiconductors [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The common point between these areas of physics is the description of these defects made by the Volterra process [1,2,4,5]. Up to now, a great deal of study has explored quantum system in the presence of disclinations [6][7][8][9][10] and screw dislocations [5,[11][12][13][14][15][16] in the context of condensed matter physics. In particular, torsion effects related to the presence of topological defects are in the interests of studies of semiconductors [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Hall effect [73], quantum scattering [74][75][76], spin currents [77], cylindrical shells [78] and geometric quantum phases [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…We consider the quantum Hall effect which is one of the most profound phenomena * Electronic address: makainca@yeah.net of charge carries in electromagnetic fields. It is shown that the Hall conductivity receives a correction which depends linearly on the scale parameters of the topological defects, and are in the same order with the corrections on the spin-Hall conductivity [22,23]. However, we can expect that very steady and precise quantized Hall conductivity can provide better experimental sensitivity and can bound on parameters of the models.…”
Section: Hua-wei Fanmentioning
confidence: 99%
“…Various studies on the electromagnetic dynamics of the magnetic and electric dipole moments shown that both their global and local physical properties can be sensitive to non-trivial geometries [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. However, it is still difficult to observe them experimentally.…”
Section: Hua-wei Fanmentioning
confidence: 99%